2020
DOI: 10.1111/nhs.12734
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses exposed to sustainability education can challenge practice: A cohort study

Abstract: Climate change will adversely affect the health of populations and the ability of healthcare systems to deliver appropriate and timely care. Furthermore, resource scarcity requires nurses to practice in more sustainable ways. This study investigated the extent to which student nurses reported that they were able to apply their knowledge of sustainability in clinical practice following educational sessions on relevant topics. Students were exposed to scenario‐based sustainability education in years 1, 2, and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Other studies show that nursing education should include environmental issues in its curriculum. 24,42,43 In addition to nursing, there is need for education regarding climate change and its health impacts for medical programs. 23,24,44,45 These findings support Nightingale's theory of environment as nature has been challenged by climate change and this has impacted human health and nursing practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies show that nursing education should include environmental issues in its curriculum. 24,42,43 In addition to nursing, there is need for education regarding climate change and its health impacts for medical programs. 23,24,44,45 These findings support Nightingale's theory of environment as nature has been challenged by climate change and this has impacted human health and nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies about sustainability in nursing education in Europe. 42,43 All these studies show that there is need for education in environmental issues in nursing.…”
Section: Discussionmentioning
confidence: 99%
“…8 We sometimes get entrenched in our own set archaic ways and views from these new nurse students may provide a fresh insight of our training and care shortcomings. 9 It may be useful to harness the views of these early years of the new nurses, who perhaps know more about the way doctors and other HPs work and deal with their patients, thus improving our patient care and the way we deal with these junior-most, but key players of our teams. 10 Based on the above surmises, the objective of this study was to administer a survey to our student nurses and assess their views about how they perceive the way the doctors and senior HPs work in our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Anåker & Elf (2014, p.387) Cruz et al (2018) suggest that increased awareness about climate change and sustainability can motivate nurses to adopt sustainable practices; this includes waste management in the clinical environment (Nichols & Mukonoweshuro, 2017). Aronsson et al (2020) found that educational sessions that focused on the relevance of climate change and sustainability to health and health care in undergraduate courses could lead nursing students to challenge unsustainable clinical practice. However, barriers to doing so included a resistance to change amongst clinical staff, in some cases related to negative staff attitudes (Aronsson et al, 2020).…”
mentioning
confidence: 99%
“…Aronsson et al (2020) found that educational sessions that focused on the relevance of climate change and sustainability to health and health care in undergraduate courses could lead nursing students to challenge unsustainable clinical practice. However, barriers to doing so included a resistance to change amongst clinical staff, in some cases related to negative staff attitudes (Aronsson et al, 2020). To learn about climate change and sustainability, Cruz et al (2018) suggest that nursing students need positive attitudes towards these concepts, including a sense of responsibility, a willingness to change and a confidence in the future (Lopez-Medina et al, 2019).…”
mentioning
confidence: 99%